Examining the Relationship Between Food Insecurity and Family Violence: a Systematic Narrative Review - McKay, Fiona H. (Journal of family violence, 2025)
PurposeThis review aimed to investigate and describe the current research that has reported on family violence and food insecurity and to explore any links. Research is beginning to explore the relationship between food insecurity and family violence, as such, this is a good time to review the current body of literature to identify existing gaps.MethodsThis research employed a narrative systematic review allowing for a broad search while maintaining methodological rigour. Key word searches were performed in 6 electronic databases in January 2023. Two overarching concepts were used: “family violence” and “food security”. The findings were synthesised into a narrative review, reporting on specific population groups separately.ResultsThe search generated 1724 articles, of which 868 were duplicates. The titles and abstracts of 856 articles were screened; 765 articles were excluded because they did not investigate the experience of food insecurity and family violence. The full text of 91 articles was reviewed, with 32 included in this review. Most were from the USA, and most employed qualitative or mixed methods. Studies explored food insecurity and family violence in women, men and women, children, people who are HIV positive, and the relationship between the COVID-19 pandemic and food insecurity.ConclusionsFood insecurity and family violence are significant societal problems, with evidence that both have increased in prevalence and severity due to the onset of the COVID-19 pandemic. This review provides initial evidence for a bi-directional relationship between food insecurity and family violence in high income countries.